Ol’ga V. Slivickaja, L’ottica di Tolstoj (ENTHYMEMA, 2012)
We provide here the translation of Ol’ga Vladimirovna Slivickaja’s essay Il sistema ottico dell’Anna Karenina: approcci al tema della modernità dell’antropologia tostoiana, that will be published in June 2012 in “Jasnopoljanskij Sbornik” n. 26. The essay proposes a focalisation of Tolstoy’s novel Anna Karenina, with particular attention to how the change of the point of view influences the representation of characters. The author investigates the optics of the distance from which the tolstoyan heroes are observed: which optics changes depending on the specific communicative intentions of the different parts of the novel.